Islamic Religious Education Values for Students Who Do Not Obey School Rules in Class VII SMPN of 16 Central Buton - Ziana, Nur; Basri, Basri; Jusu, La (Journal of English Language and Education, 2025)
Religious education is an education system that covers all aspects of life needed by humanity in order to improve the appreciation and experience of religion in social, religious, national and state life. At the junior high school level, the value of Islamic religious education needs to be applied in the learning process in order to form a good, obedient and disciplined personality. In implementing this research, it is expected to improve religious values for students who do not obey school rules and regulations that have been set in the classroom. A qualitative approach is the method used in this study. Researchers conducted observations to directly observe the objects to be studied, then conducted interviews to obtain data or information directly from respondents and finally documentation, namely collecting photos, videos, or written items if necessary. From the results of the study related to the value of Islamic religious education for students who do not obey school rules, there are still many students who pay less attention to the teacher during the learning process. In the classroom, many students still play and make noise when the teacher explains the lesson. From this, teachers are only able to provide advice or suggestions to students and do not give punishment or sanctions, because teachers are afraid that students will report to their parents if they are punished, and sometimes students report to their parents by exaggerating that the punishment given by the teacher is very severe and difficult. Through interviews, many students also dislike Islamic religious education subjects.